2020
DOI: 10.1038/s41380-020-0673-0
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and systematic review of ADGRL3 (LPHN3) polymorphisms in ADHD susceptibility

Abstract: The gene encoding adhesion G protein-coupled receptor L3 (ADGRL3, also referred to as latrophilin 3 or LPHN3) has been associated with ADHD susceptibility in independent ADHD samples. We conducted a systematic review and a comprehensive meta-analysis to summarize the associations between the most studied ADGRL3 polymorphisms (rs6551665, rs1947274, rs1947275, and rs2345039) and both childhood and adulthood ADHD. Eight association studies (seven published and one unpublished) fulfilled criteria for inclusion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Family-based and genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) in the DRD4 gene associated with ADHD [43,[79][80][81][82][83][84][85]. Furthermore, genetic variants in the FGF1 [17,52] and ADGRL3 (LPHN3) [17,52,58,59,83,[86][87][88][89][90][91][92][93] genes are associated with ADHD and ADHD endophenotypes. Other endophenotype-associated genes include DAT1, COMT, DBH, MAOA, DRD5, ADRA2A, GRIN2A, BDNF and TPH2 [94,95].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family-based and genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) in the DRD4 gene associated with ADHD [43,[79][80][81][82][83][84][85]. Furthermore, genetic variants in the FGF1 [17,52] and ADGRL3 (LPHN3) [17,52,58,59,83,[86][87][88][89][90][91][92][93] genes are associated with ADHD and ADHD endophenotypes. Other endophenotype-associated genes include DAT1, COMT, DBH, MAOA, DRD5, ADRA2A, GRIN2A, BDNF and TPH2 [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…Numeric sense has been considered a non-verbal skill that involves spatial relationships between numbers at the mental level [151]. This information is represented and processed by regions of the bilateral lobes (i.e., inferior parietal lobe and precuneus), frontal-striatal and mesial temporal activation, and by the prefrontal (i.e., superior and medial frontal gyri) and inferior frontal and intraparietal sulcus [151][152][153], where ADGLR3 is expressed [89]. As calculation tasks become more complex, there is a greater activation of the frontal region and cortical regions that underlie magnitude processing [154,155], which are important for numerical, visual and attentional processing [156][157][158], and the representation of the semantic aspect of quantity [159], which is directly related to working memory, including visual processing, speech understanding and episodic memory [160,161].…”
Section: Discussionmentioning
confidence: 99%
“…Still, readers should take them with caution because they did not survive the correction for multiple testing. In this regard, a recent meta-analysis has found that ADGRL3 haplotypes confer a relevant risk in pediatric ADHD, but results were less significant in adult ADHD 9 . The meta-analysis and our study investigated different phenomena, www.nature.com/scientificreports/ as the former reviewed studies of the association between the haplotypes and ADHD, and the latter investigates their brain correlates.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were still able to detect hypo-activations that were very statistically significant, or in other words, very unlikely due to chance. www.nature.com/scientificreports/ Third, our sample included adults, and a recent meta-analysis reported that the effects of ADGRL3 haplotypes depend on age 9 . Finally, we scanned the individuals in a 1.5 T device, and the functional sequence had a thickness of 7 mm with a 0.7 mm gap.…”
Section: Discussionmentioning
confidence: 99%
“…However, interestingly, the trans-interaction of the two classes of GPCR-LRRFn plays a role in closely related neural circuits (Figures 1C-G). Since there have been detailed reviews about Lphn3-or Lphn3-Flrt3 interaction (Figure 1G; Ranaivoson et al, 2015;Knapp and Wolfrum, 2016;Dunn et al, 2019a;Bruxel et al, 2020), this article is focused on the Elfn-mGluR interaction and its relevance to Flrt-Lphn trans-interaction.…”
Section: Introductionmentioning
confidence: 99%